A Multidisciplinary Approach to Detecting and Responding to Elder Mistreatment: Creating a University-Community Partnership - Blowers, Anita N. (American journal of criminal justice, 2012)
As the aging population grows, the problem of elder mistreatment is escalating. Cases of elder mistreatment are anticipated to increase further as the—baby boomers age and the number of elderly individuals living and receiving care at home increases (Stiegel 2006 ; Kennedy 2005 ; Meeks-Sjostrom 2004 ). While there has been increasing attention placed on understanding the dynamic of elder mistreatment, advancement of public policy and scholarly work has been hampered due to the fact that much of this work occurs in disciplinary silos. This paper spotlights one example in which university scholars from various disciplines partnered with social service providers, legal professionals, and healthcare educators in the community to enhance the development of a sustainable comprehensive elder justice network.